First‐Line Treatment of Symptomatic Subocclusive Large‐Vessel Stroke: Results of a Nationwide StrokeNet Survey - Yasmin N. Aziz; Pablo Harker; Felipe Ayala; Laura M.C. Ades; Vaibhav Vagal; Pooja Khatri (Stroke: Vascular and Interventional Neurology)
Background Limited evidence is available for the treatment of acute symptomatic subocclusive lesions in ischemic stroke. We sought to identify current treatment patterns of stroke teams at academic health centers. Methods We conducted an email survey of the National Institutes of Health StrokeNet regional coordinating centers (RCCs). Each RCC principal investigator was asked to nominate a local stroke interventionalist, or a neurologist if the RCC principal investigator was an interventionalist, most aligned with the typical practice pattern of the RCC's lead hospital, to receive a survey. The survey consisted of a clinical vignette and displayed a subocclusive lesion in the left middle cerebral artery on computed tomography angiogram followed by subsequent scenarios, revising only 1 historical, clinical, or radiographic variable at a time. Participants were asked to select initial management for each scenario. Results were reviewed and analyzed by stroke‐trained physicians. Results Responses were received from 42 (77.8%) of 54 surveyed individuals, representing 25 (92.6%) of 27 RCCs nationwide, including 25 (59.5%) interventionalists. The majority (76.2%) of respondents treated the patient in the primary clinical vignette with mechanical thrombectomy. Among all 6 clinical scenarios, respondents chose mechanical thrombectomy with or without medical management as first‐line treatment for 4 (67%) vignettes. Exceptions were low National Institutes of Health Stroke Scale score and known ipsilateral stenosis, where respondents chose medical management as first‐line treatment. Conclusion Despite limited evidence to support mechanical thrombectomy versus other treatment strategies, the majority of StrokeNet RCC respondents would use mechanical thrombectomy with or without medical therapy to treat acute ischemic stroke due to intracranial subocclusive lesions.